2020
DOI: 10.18257/raccefyn.1052
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors driving phytoplankton biomass and diversity in a tropical reservoir

Abstract: We determined the spatial and temporal variation of phytoplankton biomass and diversity in 10 fortnightly sampling journeys verifying five sampling sites in El Peñol-Guatapé reservoir located in Antioquia, Colombia. In situ and ex situ physical and chemical variables were measured and phytoplankton samples were taken. Richness was dominated by Chlorophyta and biomass by Dinophyta. This variable was higher in the transition zone while in the riverine zone it showed average values, the lowest were registered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
1
0
2
Order By: Relevance
“…The river sections of the reservoirs are characterized by inputs of large amounts of nutrients, but light attenuation and general lotic conditions limit cyanobacterial growth, in agreement with the results of similar studies [81,82,84,86,89,90]. On the other hand, in the middle (transitional) and lower (lake) areas of reservoirs, conditions such as slowing down of water-flow speed, higher sedimentation of suspended solids, and, as a result, higher transparency, better penetration of light through the water column, and heating of water masses favour cyanobacterial growth.…”
Section: Spatial Distribution Of Cyanobacterial Blooms In the Kyiv An...supporting
confidence: 88%
See 2 more Smart Citations
“…The river sections of the reservoirs are characterized by inputs of large amounts of nutrients, but light attenuation and general lotic conditions limit cyanobacterial growth, in agreement with the results of similar studies [81,82,84,86,89,90]. On the other hand, in the middle (transitional) and lower (lake) areas of reservoirs, conditions such as slowing down of water-flow speed, higher sedimentation of suspended solids, and, as a result, higher transparency, better penetration of light through the water column, and heating of water masses favour cyanobacterial growth.…”
Section: Spatial Distribution Of Cyanobacterial Blooms In the Kyiv An...supporting
confidence: 88%
“…On the other hand, in the middle (transitional) and lower (lake) areas of reservoirs, conditions such as slowing down of water-flow speed, higher sedimentation of suspended solids, and, as a result, higher transparency, better penetration of light through the water column, and heating of water masses favour cyanobacterial growth. Moreover, higher nutrient concentrations and ratios contributed to an increase in phytoplankton abundance and species richness, in particular of cyanobacterial species, as also found in previous studies [79,81,84,89,90]. Canonical correspondence analysis (CCA) showed that higher concentrations of nitrogen compounds and lower concentrations of phosphorus compounds contributed to the increase in phytoplankton biomass.…”
Section: Spatial Distribution Of Cyanobacterial Blooms In the Kyiv An...supporting
confidence: 81%
See 1 more Smart Citation
“…Interaction between the instability of the physicochemical variables and the instability of zooplankton density (based on artificial intelligence algorithms from the FCA analysis). Como se ha encontrado en diferentes estudios (Gil-Guarín et al, 2020;Ríos-Pulgarín et al, 2020), la comunidad fitoplanctónica de los embalses está estrechamente relacionada con la disponibilidad de nutrientes esenciales, como el nitrógeno para la síntesis de proteínas y la producción primaria (Roldán & Ramírez-Restrepo, 2022). En este sentido y según lo encontrado por Unrein (2001), el incremento en la densidad de Cryptomonas sp.…”
Section: Discussionunclassified
“…Trabajos basados en modelos estadísticos multivariados (Gil-Guarín et al, 2020;Pineda et al, 2022;Villabona-González et al, 2020) explican cómo las comunidades planctónicas responden a la variabilidad ambiental en los embalses. Frecuentemente estos estudios han empleado análisis estadísticos clásicos como Métodos: Se analizaron datos de variables físicas y químicas y de las densidades del fitoplancton y del zooplancton, medidas entre 2010-2018, en los embalses oligotróficos Punchiná y San Lorenzo y, entre 2013 y 2015, en el embalse hipereutrófico Porce II y en el embalse eutrófico Porce III (total N = 248).…”
Section: Introductionunclassified